2016
DOI: 10.2196/jmir.4752
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Three Modalities of Internet-Based Psychotherapy for Non–Treatment-Seeking Online Problem Gamblers: A Randomized Controlled Trial

Abstract: BackgroundInternet-based interventions targeted at the most at-risk gamblers could reduce the treatment gap for addictive disorders. Currently, no clinical trial has included non–treatment-seeking patients who have been recruited directly in their gambling environment. This study was the first exclusively Internet-based randomized controlled trial among non–help-seeking problem gamblers with naturalistic recruitment in their gambling environment.ObjectiveThe aim of this study was to assess the efficacy of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 31 publications
2
75
1
5
Order By: Relevance
“…the Our Relationship program, on‐line help for couples with sexual dysfunction, expectant couples and for children with mental health problems and their care‐givers . Several studies have investigated internet‐based interventions involving only the gambler …”
Section: Introductionmentioning
confidence: 99%
“…the Our Relationship program, on‐line help for couples with sexual dysfunction, expectant couples and for children with mental health problems and their care‐givers . Several studies have investigated internet‐based interventions involving only the gambler …”
Section: Introductionmentioning
confidence: 99%
“…Specific gambling related harms scales included the Problem Gambling Severity Index (PGSI) [6] [12] [22] [16] [23], Gambling Attitudes Scale (GAS) [7], South Oakes Gambling Screen (SOGS) [20], SOGS-R [19], and SOGS-RA [7], National Opinion Research Center DSM Screen for Gambling Problems (NODS) [8] [9] [11], Problem Gambling Significant Other Impact Scale (PG-SOIS) [13] and the Diagnostic and Statistical Manual for Mental Disorders criteria for pathological gambling (DSM IV) [6]. Of these scales the PGSI and the NODS were the most popular.…”
Section: Methodsmentioning
confidence: 99%
“…The authors note that this may have been due to recruiting players from an online casino website and that these participants were not seeking help [16]. Another RCT design study found that normative feedback did not offer significantly different reductions in gambling behaviours compared to controls [14].…”
Section: Principle Findingsmentioning
confidence: 99%
“…Diese Hilfeformen sind jederzeit verfügbar, kostengünstig und bewahren die Anonymität [51,60,61]. Bereits erwähnte Online-Eigentests, welche die Internet-Spieler in Form von Popup-Nachrichten erreichen, sind vorgesehen als Einstieg in eine Internetbasierte Kurzintervention über Chat oder E-Mail [49,62].…”
Section: Hilfesucheverhalten Und Therapieangeboteunclassified